PSYCHOLOGICAL ASPECTS OF TEACHING ENGLISH AT MIDDLE SCHOOLS IN UZBEKISTAN - Bakhronova M.A. (Western European Studies, 2024)
The global landscape has seen a significant shift in the last couple of decades, with English emerging as a main subject at schools in Uzbekistan. For countries like Uzbekistan, where English is increasingly becoming a key component of education, understanding the psychological aspects of teaching this language, especially at the middle school level, is crucial. This article explores the psychological considerations that educators need to navigate in order to facilitate effective English language acquisition among middle school students in Uzbekistan
Keywords: Middle school; psychological; mindset; motivation